Live Streams on Twitch Help Viewers Cope With Difficult Periods in Life - de Wit, Jan; van der Kraan, Alicia; Theeuwes, Joep (Frontiers in Psychology, 2020)
Live streaming platforms such as Twitch that facilitate participatory online communities have become an integral part of game culture. Users of these platforms are predominantly teenagers and young adults, who increasingly spend time socializing online rather than offline. This shift to online behavior can be a double-edged sword when coping with difficult periods in life such as relationship issues, the death of a loved one, or job loss. On the one hand, platforms such as Twitch offer pleasure, distraction, and relatedness with others to help with coping, and the increased sense of anonymity and control could stimulate self-disclosure. However, the prevalence of trolling and memes may also discourage people from opening up, and relationships that are built online — especially those with microcelebrity streamers — could be perceived as more meaningful than they actually are. To create a deeper understanding of Twitch as a new media platform embedded in game culture, and how users perceive its potential as a coping mechanism, we have conducted a first exploration by means of a survey. The questions focused on general Twitch behavior, the difficult period in life, and the role of Twitch during this period. It was distributed online among people who considered themselves active Twitch users, and who had gone through a difficult period. Eighty-four participants completed the entire survey. The majority of participants indicated that Twitch helped them cope, and that it became a larger part of their lives during the difficult period compared to regular viewing. Recurring themes were the entertainment, distraction, and sense of community Twitch offers. Viewing behavior during difficult periods appears to remain largely the same in terms of the streamers that are watched, although time spent viewing increases, and there is a change towards more time spent actively watching rather than having the stream on in the background. With this work, we aim to create a deeper understanding of Twitch as a platform, and its importance for gamers that are going through difficult periods in life.